Chemical characterisation, in vitro antioxidant, cytotoxicity and safety evaluation of Polystichum braunii (Spenn.) fee roots. Issue 24 (17th December 2021) - Saleem, Ammara; Saleem, Mohammad; Akhtar, Muhammad Furqan; Rasul, Azhar; Baig, Mirza Muhammad Faran Ashraf
Abstract: The study was intended to find in vitro antioxidant, cytotoxicity and safety profile of Polystichum braunii roots extracts and chemically characterise it by GC–MS and FTIR spectroscopy. Acute and sub-chronic (90-day oral repeated dose at 150, 300 and 600 mg/kg) toxicity studies of P. braunii methanol extract (PBME) were performed in Wistar rats by adopting OECD guidelines. The PBME exerted the highest in vitro antioxidant potential. There was no substantial change in blood parameters and body weight except a notable ( p < 0.01) rise in ALT, ALP, MDA and HDL, and decrease in cholesterol and LDL ( p < 0.05) in animals sub-chronically treated with PBME at 600 mg/kg dose. The IC50 in HepG2 was more than 1000 µg/ml. The GC–MS analysis revealed Pentadecanoic acid and 9, 12-Octadecadienoic acid in PBME. The P. braunii might be safe in acute usage, however, monitoring of liver function tests should be carried out during long-term use. Abstract : UF0001